2005
DOI: 10.1111/j.1471-0528.2005.00794.x
|View full text |Cite
|
Sign up to set email alerts
|

General obstetrics: Does size matter? A population‐based study of birth in lower volume maternity hospitals for low risk women

Abstract: Objective  To study the association between volume of hospital births per annum and birth outcome for low risk women.Design  Population‐based study using the National Perinatal Data Collection (NPDC).Setting  Australia.Participants  Of 750,491 women who gave birth during 1999–2001, there were 331,147 (47.14%) medically ‘low risk’ including 132,696 (40.07%) primiparae and 198,451 (59.93%) multiparae.Methods  The frequency of each birth and infant outcome was described according to the size of the hospital where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 48 publications
1
83
1
4
Order By: Relevance
“…Typically it was the smaller units, performing less than 500 births, which closed (n = 255 nationally). It is likely that these were in rural and remote areas 1,3,8,44 though this cannot be determined from this data. The findings demonstrate the centralisation of maternity services, in Queensland in particular, where the number of hospitals performing more than 2001 births doubled (from 5 to 10).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Typically it was the smaller units, performing less than 500 births, which closed (n = 255 nationally). It is likely that these were in rural and remote areas 1,3,8,44 though this cannot be determined from this data. The findings demonstrate the centralisation of maternity services, in Queensland in particular, where the number of hospitals performing more than 2001 births doubled (from 5 to 10).…”
Section: Discussionmentioning
confidence: 81%
“…The decline of maternity units is a long-term trend which has been reported in the literature across many countries and results in some women living considerable distances from services, especially those in rural and remote areas. [1][2][3][4]7,8,10,11,23,31,32,35,45 This study has identified a significant inverse association between the supply of maternity units and the BBA rate in Queensland and Australia. Identifying the exact geographic location of the mothers usual residence was not possible without geocoded data, which is not freely available.…”
Section: Discussionmentioning
confidence: 98%
“…The reopening of small units needs to be accompanied by strategies to enable health professionals, including midwives, to practise confidently and safely as, contrary to commonly held beliefs, lower hospital volume has not been shown to be associated with increased adverse outcomes for healthy women. 25 …”
Section: Recommendationsmentioning
confidence: 97%
“…Previous research has analyzed hospital obstetric volume, [1][2][3][4][5] institutional characteristics (eg, academic affiliation), 6 and timing of delivery (hour, day, and month). [7][8][9][10][11][12][13] Although results vary, each of these factors has been associated with both the practice of obstetrics and the frequency of adverse birth outcomes.…”
mentioning
confidence: 99%